Role of Cognitive Radio on 4G Communications A Review - Kumar, Neeraj; Singla, Ayush (IJRDO -Journal of Computer Science Engineering, 2015)
There is a rapid advancement in wireless communication technology providing the network services anywhere and anytime. 4G communication systems are being developed to solve the various problems the current communication systems (3G, 2.5G) are facing.4G will be an intelligent technology that will reduce the number of different technologies to a single global standard. Cognitive Radio (CR) is the key enabling technology for next generation networks. Cognitive Radio techniques provide the capability to use or share the spectrum in an opportunistic manner. With the use of CR, 4G wireless networks will support global roaming across multiple wireless and mobile networks. In this paper, the Role of CR in 4G Communications is reviewed. The recent research being done on Cognitive Radio and 4G technologies is identified. The main possibilities of implementing Cognitive Radios in 4G Communication Systems are surveyed. IEEE 802.22 networks are cognitive technology based networks which will enhance the performance of 4G Communication systems. IEEE 802.16h (WiMAX) provide extensions to support unlicensed coexistence. Keywords: Cognitive Radio (CR), WiMAX, 4th Generation (4G)